2015
DOI: 10.1093/nar/gkv536
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of RNA cleavage by 5′-hydroxyl RNA sequencing

Abstract: RNA cleavage by some endoribonucleases and self-cleaving ribozymes produces RNA fragments with 5′-hydroxyl (5′-OH) and 2′,3′-cyclic phosphate termini. To identify 5′-OH RNA fragments produced by these cleavage events, we exploited the unique ligation mechanism of Escherichia coli RtcB RNA ligase to attach an oligonucleotide linker to RNAs with 5′-OH termini, followed by steps for library construction and analysis by massively parallel DNA sequencing. We applied the method to RNA from budding yeast and captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 66 publications
(96 reference statements)
1
41
0
Order By: Relevance
“…In this case, ribothrypsis products are immediately accessible to XRN1, which degrades RNAs bearing 5′-P, and ribothrypsin is likely a protein whose cleaved products bear 5′-P (3′-fragment) and 3′-OH (5′-fragment). However, we note that the Hesselberth lab was able to selectively capture and sequence, from budding yeast, the small amounts of RNAs bearing 5′-OH termini by employing RtcB RNA ligase and found that such fragments originated from CDS regions of numerous mRNAs 60 . Intriguingly, 5′-OH fragments seemed to accumulate upstream of codons for acidic and basic aminoacids 60 .…”
Section: Discussionmentioning
confidence: 94%
“…In this case, ribothrypsis products are immediately accessible to XRN1, which degrades RNAs bearing 5′-P, and ribothrypsin is likely a protein whose cleaved products bear 5′-P (3′-fragment) and 3′-OH (5′-fragment). However, we note that the Hesselberth lab was able to selectively capture and sequence, from budding yeast, the small amounts of RNAs bearing 5′-OH termini by employing RtcB RNA ligase and found that such fragments originated from CDS regions of numerous mRNAs 60 . Intriguingly, 5′-OH fragments seemed to accumulate upstream of codons for acidic and basic aminoacids 60 .…”
Section: Discussionmentioning
confidence: 94%
“…Both processes have been observed on ORF-internal polylysine reporters as well as reporters where the ribosome translates authentic poly(A) tail (Tsuboi et al 2012;Shao et al 2013;Shcherbik et al 2016). More generally, runs of polybasic residues in the genome have been reported to increase mRNA cleavage, possibly due to the NSD/NGD pathway (Peach et al 2015). However, it remains unclear whether these pathways operate independently or specialize for particular substrates.…”
Section: Introductionmentioning
confidence: 99%
“…PNKs target the 5 ′ -terminus of DNA and RNA substrates and catalyze the transfer of the γ-phosphate from nucleoside triphosphate (NTP) to the 5 ′ -hydroxyl terminus of the polynucleotide substrate. The 5 ′ -phosphorylation status of DNA and RNA is critically important in the cell, thus underscoring the need for the PNK family of enzymes (Peach et al 2015). For example, phosphorylation of 5 ′ -hydroxyl termini following DNA damage is required for subsequent DNA repair (Weinfeld et al 2011); whereas RNA turnover by the eukaryotic Xrn 5 ′ -exonuclease family requires a 5 ′ -phosphate for RNA degradation (Heindl and Martinez 2010;Jinek et al 2011).…”
Section: Introductionmentioning
confidence: 99%